Penerapan Lafaz Haqiqah dan Majaz dalam Penetapan Hukum Keluarga Kontemporer - Yulizain Putra; Muchlis Bahar; Firdaus (STAI Pelabuhan Ratu, 2026)
In the linguistic hierarchy scheme, Haqiqah occupies a superior position compared to Majaz, because Haqiqah is the main core while Majaz is only a derivative. Consequently, Majaz should not be used as the foundation for establishing Islamic law unless Haqiqah is difficult to implement, and at that time a supporting indicator (qarinah) is needed to clearly guide it. In Arabic linguistics, the term